Downstep and Recursive Phonological Phrases in Bàsàá (Bantu A43) - Hamlaoui, Fatima; Makasso, Emmanuel-Moselly (My University, 2019)
This paper identifies contexts in which a downstep is realized between consecutive H tones in absence of an intervening L tone in Bàsàá (Bantu A43, Cameroon). Based on evidence from simple sentences, we propose that this type of downstep is indicative of recursive prosodic phrasing. In particular, we propose that a downstep occurs between the phonological phrases that are immediately dominated by a maximal phonological phrase (φmax).
Keywords: Bàsàá; phonological phrases; Cameroon; Bantu A43